2016
DOI: 10.3389/fphys.2016.00520
|View full text |Cite
|
Sign up to set email alerts
|

Amino Acid Changes at Arginine 204 of Troponin I Result in Increased Calcium Sensitivity of Force Development

Abstract: Mutations in human cardiac troponin I (cTnI) have been associated with restrictive, dilated, and hypertrophic cardiomyopathies. The most commonly occurring residue on cTnI associated with familial hypertrophic cardiomyopathy (FHC) is arginine (R), which is also the most common residue at which multiple mutations occur. Two FHC mutations are known to occur at cTnI arginine 204, R204C and R204H, and both are associated with poor clinical prognosis. The R204H mutation has also been associated with restrictive car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 40 publications
(61 reference statements)
2
5
0
Order By: Relevance
“…A previous study showed that a heterozygous mutation in the TPM2 gene resulted in a hypercontractile phenotype that is likely caused by increased calcium sensitivity of force generation [ 17 ]. Similar results are reported in patients with Tpm3.12 deletions and fast TnI mutations [ 18 , 19 ]. Increased calcium sensitivity of force generation can result in excessively sensitized cross-bridge cycling, leading to increased basal muscular tone [ 17 ].…”
Section: Discussionsupporting
confidence: 89%
“…A previous study showed that a heterozygous mutation in the TPM2 gene resulted in a hypercontractile phenotype that is likely caused by increased calcium sensitivity of force generation [ 17 ]. Similar results are reported in patients with Tpm3.12 deletions and fast TnI mutations [ 18 , 19 ]. Increased calcium sensitivity of force generation can result in excessively sensitized cross-bridge cycling, leading to increased basal muscular tone [ 17 ].…”
Section: Discussionsupporting
confidence: 89%
“…Unexpectedly, this study found that TNNI3 sarcomere gene mutations can both directly cause HCM, and also cause HCM by further changing the metabolism of cardiomyocytes. Moreover, no change was observed in the TC, TG, LDL or HDL levels in the serum of KI mice, while the corresponding indicators of TC and TG in the myocardial tissue increased, further confirming the myocardial specificity of cTnI [27] .…”
Section: Discussionmentioning
confidence: 56%
“…Of the mutations on TNNI3, the mutation at the arginine residue at position 204 is the most common mutation associated with familial HCM. The R204H mutation is also associated with restrictive cardiomyopathy (RCM) [19]. In this study, it was reported for the first time that the R204C mutation can also lead to the RCM phenotype.…”
Section: 2discussionmentioning
confidence: 93%